Illegitimacy Testing of Elaeis guineensis Population Based on Simple Sequence Repeat Markers - Lalu Firman Budiman; Ardha Apriyanto; Adi Pancoro; Sudarsono Sudarsono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Illegitimacy is a factor negatively affecting controlled pollination in Elaeis guineensis breeding programs and it may happen in any step of hybridization processes, starting from early stages of parent selection and labeling to the last stage of the replicated field trial. Availability of method for testing the existence of illegitimacy among progenies of oil palm is beneficial. Four half-sib family populations consisted of 83 individuals were evaluated. Sixteen loci of SSR markers were utilized to genotype plant materials and identify illegitimate individuals. The legitimate parents and illegitimate progenies were evaluated using CERVUS and COLONY softwares. The results showed that the 16 SSR marker loci evaluated were having medium to high PIC values and they were both informative and suitable for parent-offspring analysis. The results also showed that the 16 SSR markers were sufficient for the illegitimacy testing using the COLONY software. Moreover, this study did not find any illegitimate individual among the four progeny populations. The generated SSR marker data were also successfully used to assign and to reconstruct the expected pedigree of the progenies. This can be used as an example of molecular marker utilization to improve the integrity of breeding program of oil palms.